2010
DOI: 10.1007/s00270-010-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioma of the Interatrial Septum: CT and MRI Features

Abstract: Hemangioma of the heart is a rare primary benign tumor mainly appearing as enhancing, homogenous, well-circumscribed mass. We report a case of a 61-year-old asymptomatic woman, whose echocardiography showed a cardiac mass, which was described as the atypical myxoma of the right atrium. For further imaging, contrast-enhanced computed tomography and cardiac magnetic resonance imaging were undertaken, which showed a tumor located in the interatrial septum with imaging characteristics of hemangioma. In the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…3). The differential diagnosis for a mass in the interatrial septum includes thrombi, myxomas, lipomas, fibromas, cysts, and malignant tumors [9]. For intracardiac cystic lesions, post-traumatic cysts, hydatid cysts, blood cysts, teratomas, and cavernous lymphangioendotheliomas should be included in the differential diagnosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…3). The differential diagnosis for a mass in the interatrial septum includes thrombi, myxomas, lipomas, fibromas, cysts, and malignant tumors [9]. For intracardiac cystic lesions, post-traumatic cysts, hydatid cysts, blood cysts, teratomas, and cavernous lymphangioendotheliomas should be included in the differential diagnosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MRI in this study suggested that the lesions were of vascular origin, which facilitated the diagnosis and differential diagnosis. Typically, cardiac VM shows isointense and high signal intensity compared with myocardium in T1-and T2-weighted images, respectively (5,8,9). Homogeneous enhancement after contrast infusion is another typical manifestation of cardiac VM (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac MRI is a superior tool with a better contrast resolution 5 . Hemangiomas have an intermediate T1 signal with the same intensity as myocardium and a high T2 signal 7 . The dynamic postcontrast acquisition shows nodular enhancement with progressive fill-in on delayed images 8 .…”
Section: Discussionmentioning
confidence: 99%